A Qualitative Study of Learning Environment Quality in Rural Public Secondary Schools - Ikayani, Ikayani; Abubakar, Abubakar; Nasir, Nasir (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
This study examines the quality of the learning environment at SMP Negeri 2 Kolaka Utara by analyzing the interaction between structural, pedagogical, and socio-economic factors within a rural public secondary school context. Employing a qualitative research design, data were collected through in-depth interviews and document analysis involving the school principal, teachers, and parents, and analyzed using thematic analysis. The findings reveal that limitations in educational infrastructure, uneven development of teachers’ professional competencies, low parental engagement, and students’ socio-economic constraints jointly shape the learning environment and hinder its optimal development. Rather than functioning as isolated issues, these factors form an interconnected system that influences teaching effectiveness and student learning experiences. This study highlights that improvements in learning environment quality require an integrated, multi-stakeholder approach that aligns school management practices, teacher capacity development, and community participation. The novelty of this research lies in its holistic analytical framework, which moves beyond single-factor explanations by demonstrating how multiple dimensions simultaneously affect learning environments in rural secondary schools. The study contributes to educational management and school improvement literature by providing empirical insights that support context-responsive and sustainable strategies for enhancing learning environments in under-resourced educational settings.